The influence of tetrachloromethane on subcellular structures of rat hepatocyte lysosomal and cytoplasmic enzymes of the liver, lungs and blood serum of rats during continuous and intermittent action of tetrachloromethane - Merkureva, R V; Aulika, B V; Shaternikova, I S; Konstantinova, I N; Dolinskaya, S I; Bushinskaya, L I; Nekrasova, G I; Koganova, Z I (Journal of hygiene, epidemiology, microbiology, and immunology, 1980)
The authors performed a comparative biochemical study of some enzymes of lysosomic origin (hyaluronidase, N-acetyl-beta-D-glucosaminidase, beta-glucosidase, beta-galatosidase and acid phosphatase), of the state of enzyme substrate system N-acetylneuraminic acid---aldolase of neuramic acid and of the activity of lactatedehydrogenase (soluble in cytosol and bound on mitochodria) in the liver, lungs and blood serum of rats at various regimens of the inhalation action of CCl4. On the basis of results obtained they determined the biological importance of the change of activity of enzymes differently localized in cells at the adaptation of an organisme to the noxious action of CCl4.
Keywords: Male; hydrolasy; cytoplazma; plíce; lyzozomy; Animals; L-Lactate Dehydrogenase; aldolasa; Fructose-Bisphosphate Aldolase; chlorid uhličitý; mužské pohlaví; krysa rodu Rattus; Cytoplasm; Rats; Liver; zvířata; Lysosomes; Hydrolases; L-laktátdehydrogenasa; játra; Lung; Carbon Tetrachloride